PERANCANGAN BRAND IDENTITY UNTUK MENINGKATKAN BRAND AWARENESS KEDAI KIMBOS DI KOTA MALANG DENGAN MENGGUNAKAN METODE DESIGN THINKING - Jocelyn, Michelle; Pratama, Bintang Pramudya Putra; Sukmaraga, Ayyub Anshari (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2024)
Chicken meat is a source of high quality protein with various other nutrients needed for the human body to function properly. One of the food stalls that serves fast food chicken menus at affordable prices and delicious taste is Kedai Kimbos. Having a very strategic location, located near three private universities in Malang City, namely the Malang City College of Economics, Merdeka University, and Ma Chung University. This is very profitable, making Kedai Kimbos quite popular among students, but unfortunately Kedai Kimbos does not yet have a brand identity to expand the scope of promotion in Malang City. By using the design thinking method from a book created by Lewrick, Link, and Leifer entitled: Design Thinking Playbook, the brand identity will be created. The data collection method uses qualitative methods according to Suyitno. By using the method above, research and design flow can be carried out in a directed manner and in accordance with brand needs. After conducting research and data synthesis, Kedai Kimbos' brand identity will be designed which will then be published in a guide standard manual book containing brand concepts and values, logo, tagline, visual identity, along with its implementation on packaging, social media, and other supporting media. After carrying out production trials of the design results, the brand identity can be visualized well and can differentiate Kedai Kimbos from similar brands.